Analisis Kualitas Air Danau Mas Harun Bastari di Kabupaten Rejang Lebong Provinsi Bengkulu, Indonesia - Humairani, Humairani; Sofian, Sofian; Mulyani, Rahma; Yusanti, Indah Anggraini; Rahmadiah, Triayu; Nafsiyah, Ikromatun; Lestari, Siti; Hamka, Muhammad Subhan (Universitas Batangahari Jambi, 2026)
Lake Mas Harun Bastari is one of the important tourism lakes in Bengkulu Province with strategic ecological and economic functions. Increasing tourism and agricultural activities around the lake have the potential to affect water quality through the input of organic matter and nutrients. This study aimed to analyze the water quality status of Lake Mas Harun Bastari based on physical and chemical water parameters, as well as to identify indications of eutrophication and potential pollution sources. The study was conducted from January to February 2026 at six observation stations distributed across the northern, southern, eastern, and western parts of the lake. Sampling points were determined using a purposive sampling method based on environmental characteristics and anthropogenic activities surrounding the waters, such as tourism areas, agricultural land, and water inlet and outlet zones. Water sampling was carried out using the grab sampling method in accordance with SNI 6989.57:2008 concerning surface water sampling methods. The parameters analyzed included temperature, Total Dissolved Solids (TDS), pH, Dissolved Oxygen (DO), phosphate (PO₄-P), ammonia (NH₃), Chemical Oxygen Demand (COD), and nitrate (NO₃⁻). Data were analyzed descriptively and compared with the Class II water quality standards based on Government Regulation No. 22 of 2021. The results showed that water temperature ranged from 26.3–26.8°C, TDS 20–58 mg/L, pH 6.39–6.85, DO 5.7–6.4 mg/L, phosphate